Strong coupling corrections in the analysis of x-ray Thomson scattering measurements - Gregori, G; Glenzer, S; Landen, O (2003)
We present simplified expressions for the dynamic structure factor, or form factor S(k, omega), which is the quantity describing the inelastic x-ray scattering cross section from a dense plasma or a simple liquid. Our results, based on the random phase approximation (RPA) for the treatment on the charged particle coupling, are compared with analytical expressions for the free electron dynamic structure factor which include effects of strong coupling in both classical and degenerate plasmas. We will show that these modifications introduce minimal corrections to the RPA for typical conditions found in recent non-collective x-ray Thomson scattering experiment on solid density isochorically heated laser plasmas. On the other hand, strong collective scattering may exhibit significant deviations from the RPA. The results shown in this work can be applied to interpreting future x-ray scattering in warm dense plasmas occurring in inertial confinement fusion experiments or for the modelling of solid density matter found in the interior of planets.